Deconstructing Takfiri Narratives: A Semiotic Analysis of Nahdlatul Ulama’s Digital Discourse on NU Online - Wati, Dian Annisa Rizkyah; Mhd. Syahnan (Faculty of Ushuluddin and Philosophy, 2023)
The spread of takfiri ideology—rooted in the historical legacy of the Khawarij and Wahhabi movements—has contributed significantly to religious radicalism, threatening the internal unity of Muslims and disrupting broader social harmony. As a representative of moderate Sunni Islam (Ahl al-Sunnah wa al-Jamā‘ah), Nahdlatul Ulama (NU) has responded proactively to this challenge, particularly through its digital platform, NU Online. This study examines how NU Online constructs an anti-takfiri discourse using the semiotic theory of Charles Sanders Peirce. Applying Peirce’s triadic model—which includes the signifier (the sign), the object and the interpreter—this research analyses the signs and meanings embedded in NU’s digital content aimed at deconstructing takfiri rhetoric. Using a qualitative literature-based approach, this study finds that NU's digital messages consistently emphasize the principles of Islamic moderation, critical thinking, and a tolerant national identity. This communication strategy challenges extremist interpretations and reinforces a theological framework emphasizing peace and inclusivity while demonstrating how religious semiotics can function as a tool of ideological resistance in the digital age.